Nutrient requirement and kinetics of phenol degradation by Rhodococcus sp. UKMP-5M in batch and continuous culture using stirred tank bioreactor - Yaacob, Nor Suhaila (2013)
Rhodococcus UKMP-5M is a gram positive locally isolated strain that capable of degrading an impressive range of xenobiotic and hazardous compounds. This strain arises normally from contaminated soil and aquatic sediments which is highly enriched with the source of contamination. Phenol and its derivatives are known as one of the example of xenobiotic compound that always need to be removed from the environment. Biodegradation by microbial activity may be used as an effective method for phenol removal from the contaminated sites. The feasibility of using Rhodococcus UKMP-5M in phenol biodegradation is the main focus of this study. Nutrients requirement for the enhancement of growth of Rhodococcus UKMP-5M and the ability to degrade phenol was first studied in 250 mL shake-flask culture. The various parameters applied during the cultivation that influenced phenol biodegradation by Rhodococcus UKMP-5M were also optimized using response surface methodology (RSM) aimed at improving the biodegradation performance in terms of percentage of phenol degraded and degradation time. The performance of using cells suspended in medium containing phenol, termed as biotransformation, in biodegradation of phenol was also studied. The effect of mode of bioreactor operation (batch and continuous culture) on phenol biodegradation by Rhodococcus UKMP-5M was studied using 2 L stirred tank bioreactor. The activity of phenol hydroxylase, the enzyme responsible in phenol degradation, was evaluated in various phenol biodegradation experiments. Finally, phenol hydroxylase of Rhodococcus UKMP-5M was purified and its characteristics in phenol degradation were identified. From the initial screening of medium composition and cultivation condition, it was found that basal medium M1, temperature of 37°C, pH of 7.5, buffer concentration of 50-150 mM, ammonium sulphate concentration of 0.4 g/L and natrium chloride of 0.1 g/L gave the highest growth of Rhodococcus UKMP-5M and degradation of phenol. Rhodococcus UKMP-5M was capable to tolerate up to 900 mg/L phenol. Phenol degradation by the growing cells of Rhodococcus UKMP-5M was further improved by optimization using RSM, where the degradation period for 1 g/L phenol was successfully reduced from 48 h to 27 h with phenol concentration, ammonium sulphate and temperature were the most significant variables that influenced phenol biodegradation. Although the biotransformation using whole cells of Rhodococcus UKMP-5M in minimal salt medium (MSM) containing phenol was successfully developed for the biodegradation of phenol, but the degradation efficiency was lower than those obtained in the growing cell system. In the optimal conditions (agitation speed of 160 rpm, air flow rate of 1.5 vvm and controlled dissolved oxygen tension at 80% air saturation) for biodegradation of phenol by Rhodococcus UKMP-5M using 2 L stirred tank bioreactor, 0.5 g/L of phenol was sucessfuly degraded in 12 h of cultivation. The continuous mode of bioreactor operation was also successfully used for phenol biodegradation by Rhodococcus UKMP-5M, where the phenol degradation rate of 0.18 h -1 obtained in the continuous culture was about 70% higher than that obtained in batch mode of bioreactor operation. In all cases, high biodegradation of phenol was corresponded well with high activity of phenol hydroxylase, suggesting that this enzyme was responsible in phenol biodegradation. The cells of Rhodococcus UKMP-5M were successfully disrupted using glass bead technique for the extraction of phenol hydroxylase. The optimal cell disruption was obtained at this condition: 50 mL falcon bottle, glass bead with the diameter of 425-600 μm, cell concentration of 10%, and disruption time of 30 min. Phenol hydroxylase was purified using anion exchange chromatography by DEAE-sepharose fast flow column, which gave the purification fold and yield of 10.18 and 14.28%, respectively. The molecular weight of phenol hydroxylase was 53 kDa, while the Km and Vmax values of NADH using Lineweaver-burk plot were 16.98 µM and 28.57 U/mg protein, respectively. The optimal temperature and pH for the maximum activity of phenol hydroxylase from Rhodococcus UKMP-5M was obtained at 25oC and pH 7.5, respectively. Results of this study have demonstrated that Rhodococcus UKMP-5M is a versatile bacterium which has a great potential to be used industrially in the removal of xenobiotic compounds especially phenol.